Causal Factors Affecting the Financial Adequacy of Employed Person in Pre-Retirement Age in the Northeast - Jongwattananukul, Banlang; Tiwasasit, Atit; Ponklang, Pittaya (Journal for Developing the Social and Community, 2025)
Background and Aims: The financial adequacy of pre-retirement working individuals is influenced by several key factors, including income, consistent saving patterns, and financial behaviors that affect spending and investment decisions. Additionally, labor market stability, government welfare, and debt obligations are significant variables that determine an individual’s ability to prepare financially for retirement. Without proper financial planning, there is a risk of facing financial insufficiency in the future. This study aims to: (1) develop a causal model of factors affecting financial adequacy among pre-retirement working individuals; (2) analyze the direct influence of causal factors on financial behavior; and (3) examine the indirect influence of causal factors on financial adequacy through financial behavior as a mediating variable. Methodology: This research is a quantitative study. The sample group consisted of 456 employed individuals who are insured under Article 33 (compulsory section) of the Social Security System in the Northeastern region of Thailand. A two-stage sampling method was used, which included purposive non-probability sampling followed by stratified probability sampling. The research instrument was a questionnaire. The statistical methods used included descriptive statistics and inferential statistics for developing a structural equation model and conducting confirmatory factor analysis. The study also involved model analysis and an assessment of model fit. Results: 1) The developed model demonstrated a good fit with the empirical data, indicating that the causal model of factors influencing financial adequacy appropriately explains the relationships among the relevant variables. 2) Financial literacy has a significant direct influence on financial behavior. Financial attitude also shows a significant direct influence on financial behavior. Additionally, motivation for financial planning toward retirement has a direct effect as well. And 3) Financial literacy indirectly influences financial adequacy through financial behavior. Likewise, financial attitude has an indirect influence, and motivation for planning also indirectly affects financial adequacy. Meanwhile, financial behavior itself has a significant direct influence on financial adequacy. Conclusion: Good financial behavior leads to financial adequacy. Such behavior is influenced by psychological factors, economic conditions, and socialization factors. Therefore, the government should place importance on promoting adequate income levels for working individuals, including setting appropriate minimum wages that are sufficient to meet daily living expenses. Moreover, it is essential to enhance access to diverse financial resources in ways that do not create excessive debt burdens. Additionally, efforts should be made to encourage pre-retirement workers to develop self-awareness regarding their financial capabilities, foster satisfaction with saving, and build confidence in their financial decisions. These actions will contribute to better financial behavior and ultimately lead to appropriate levels of financial adequacy.